Results of arbovirological examination of birds of the family Hirundinidae in Czechoslovakia - Juricová, Z; Hubálek, Z; Halouzka, J; Hudec, K; Pellantová, J (Folia parasitologica, 1989)
Migratory birds (swallow, Hirundo rustica; sand martin, Riparia riparia; house martin, Delichon urbica) caught in southern Moravia (Czechoslovakia) in 1984-87 were examined for arbovirus infections. Isolation experiments were carried out using blood samples of 183 birds (52 swallows, 107 sand martins, and 24 house martins). The results were negative. Serological examinations of 136 birds (36 swallows, 86 sand martins, and 14 house martins) were made by haemagglutination-inhibition test (HIT) using 6 arboviral antigens of the genera Alphavirus (Sindbis--SIN) and Flavivirus (tick-borne encephalitis--TBE, West Nile--WN) and of the family Bunyaviridae (Tahyna--TAH, Calovo, CVO, and Bhanja--BHA). Antibodies against all of the tested viruses were detected at different rates: SIN 2.9%, TBE 1.5%, WN 1.5%, TAH 4.4%, CVO 1.5%, and BHA 2.2%. The titres ranged from 1.20 to 1.80.
Keywords: Czechoslovakia; protilátky virové; Arboviruses; Arbovirus Infections; Bunyaviridae; Alphavirus; nemoci ptáků; ptáci; Birds; arbovirové infekce; Animals; Flavivirus; zvířata; Československo; Bird Diseases; Hemagglutination Inhibition Tests; Antibodies, Viral; testy inhibice hemaglutinace; arboviry